Implementasi Konsep “Blue Economy” Dalam Meningkatkan Pendapatan Nelayan Di Kota Medan Perspektif Ekonomi Syariah (Studi Kasus:Kecamatan Medan Labuhan) - Alfaqih Tariq Aziziy Hasibuan; Rahmi Syahriza; Muhammad Syahbudi (Jurnal Ekonomi dan Bisnis Digital, 2023)
Blue Economy is ecosystem-based management to take full advantage of well-managed marine resources to carry out cross-sectoral coordination with public-private partnerships and investments that will provide benefits for the country's economic income by continuing to develop the future potential of marine-based economic resources. The blue economy can create great opportunities to overcome problems in coastal areas by overcoming the challenges they pose. The aim of this research is to determine the implementation of the "Blue Economy" concept in increasing fishermen's income in Medan City. to find out the implementation of the "Blue Economy" concept from a sharia economic perspective. This research is qualitative field research. The subjects of this research are traditional fishermen in Nelayan Indah Village, Medan Labuhan District, while the object of this research is the marine ecosystem in Kurnia Village, Medan Labuhan District. The result of this research is the implementation of the "Blue Economy" concept in increasing fishermen's income in Medan City. 1. The provincial, sub-district and fishermen governments of Medan Labuhan sub-district have not contributed much in terms of implementing blue economy indicators. 2. The concept of minimizing waste has not been properly actualized, not many processed products have been created. 3. Social inclusion has been widely implemented by the government, in this case the Ministry of Maritime Affairs and Fisheries, to improve the welfare of fishermen. 4. Innovation and adaptation in marine matters and protecting the ecosystem are still very minimal. 5. The multiplier effect by creating processed seafood products is still very minimal. 6. Public awareness of protecting the environment and marine ecosystems is also still low. The implementation of the "Blue Economy" concept is in accordance with the sharia economic perspective, where Islam is very concerned about environmental sustainability.